2014
DOI: 10.4103/0974-1208.138874
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endometriosis on implantation rates when compared to tubal factor in fresh non donor in vitro fertilization cycles

Abstract: OBJECTIVE:The objective of the following study is to compare the outcome of in vitro fertilization and embryo transfer (IVF-ET) in women with endometriosis and tubal-factor infertility.DESIGN:Retrospective study.SETTING:Tertiary referral hospital, assisted reproductive technologies unit.MATERIALS AND METHOD:The study group consisted of 78 women diagnosed with advanced stage endometriosis. The control group included 100 women with tubal-factor infertility. These groups were retrospectively analyzed regarding st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 27 publications
2
19
0
10
Order By: Relevance
“…18 In a meta-analysis, Barnhart et al found that the implantation and clinical pregnancy rates were lower in the EM group than in the control group. 1 Similar to these findings, we found that 20 The number of oocytes retrieved and the fertilization rate were significantly lower in the EM group than in the tubal group, but there was no significant difference in the percentage of metaphase II (M2) oocytes, cleavage rate, and percentage of grade 1 embryos formed between the 2 groups. Moreover, the mean number of embryos transferred did not differ between the 2 groups.…”
Section: Discussionsupporting
confidence: 79%
“…18 In a meta-analysis, Barnhart et al found that the implantation and clinical pregnancy rates were lower in the EM group than in the control group. 1 Similar to these findings, we found that 20 The number of oocytes retrieved and the fertilization rate were significantly lower in the EM group than in the tubal group, but there was no significant difference in the percentage of metaphase II (M2) oocytes, cleavage rate, and percentage of grade 1 embryos formed between the 2 groups. Moreover, the mean number of embryos transferred did not differ between the 2 groups.…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, evidence that reduced fertility in endometriosis is exerted through the oocyte, and not other factors is accumulating4. For instance, implantation and pregnancy rate are not significantly different in patients with endometriosis compared to controls when undergoing IVF and embryo transfer56. Further evidence comes from oocyte donor studies: control donor oocytes were equally likely to implant in patients with endometriosis as without78, whilst oocytes from women with endometriosis were less likely to implant than those without9.…”
mentioning
confidence: 99%
“…U SAD se stopa živorođenosti posle IVF/ET postupaka kod pacijentkinja sa endometriozom kreće oko 39,1%. To je u suprotnosti sa metaanalizama koje pokazuju manju sto-pu trudnoća posle IVF kod pacijentkinja sa infertilitetom uzrokovanim endometriozom nego kod onih sa tubarnim faktorom [7,27]. Osim toga, stopa trudnoća je manja kod onih sa težim formama endometrioze nego kod onih sa minimalnom i blagom endometriozom [7].…”
Section: Endometrioza I Art -Preporuke Asrmunclassified